If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = p + -36 Reorder the terms: 4 = -36 + p Solving 4 = -36 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 4 + -1p = -36 + p + -1p Combine like terms: p + -1p = 0 4 + -1p = -36 + 0 4 + -1p = -36 Add '-4' to each side of the equation. 4 + -4 + -1p = -36 + -4 Combine like terms: 4 + -4 = 0 0 + -1p = -36 + -4 -1p = -36 + -4 Combine like terms: -36 + -4 = -40 -1p = -40 Divide each side by '-1'. p = 40 Simplifying p = 40
| -7+8p=-7-2p | | 8v-(8v-6)= | | -12-5y=-32 | | √25/289 | | 6x2/3x | | 5/6=1/2v | | -5-6(k+5)=-(k-5) | | 3a+7-8a= | | 6x+1=10x-1 | | 100+20(5.25)=x | | 3(w+1)=w+19 | | 6(x-1)=-3+6(x+8) | | (-4)-((-9/-9)-8) | | x^2=100-15x | | 159+12x=96-5x | | -29m=-1131 | | X-3X+4+8=X | | -40-6n=-3(8n-3) | | 7+3-4m=9 | | -7x-6y-4x+7y= | | -3x-(x-8)=-7-7x | | 144/16 | | 37+3v=2(4v+1) | | (6x+5)+(4x-2)=8x+21 | | 8x+77= | | 2m+15=31 | | (2x+4)+5=11 | | -35=x-37 | | 9-4x+x=-6 | | 10r-2=6 | | -4n-7n= | | 7(3d-11)=-35 |